2018
DOI: 10.1021/acs.organomet.8b00674
|View full text |Cite
|
Sign up to set email alerts
|

Ta-Catalyzed Hydroaminoalkylation of Alkenes: Insights into Ligand-Modified Reactivity Using DFT

Abstract: Density functional theory (DFT) calculations were performed to probe the mechanism of tantalum-catalyzed hydroaminoalkylation, a reaction that affords Csp3–Csp3 bond formation via α-alkylation of a secondary amine with an alkene. Electronic effects in catalyst design were probed to reveal key features in the energy profile of the proposed mechanism, corroborating experimental trends in which electrophilic metal centers demonstrate enhanced reactivity. Modeling of the energy profile with an N,O-chelating amidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
40
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 50 publications
6
40
0
Order By: Relevance
“…In the formation of intermediate D two diastereomers can result ( D and D′ ), with the trans-orientation of the metallacyclic intermediates giving the major diastereomer . This is consistent with computational investigations of early transition-metal-catalyzed hydroaminoalkylation , which propose that polarized, activated alkenes, such as vinyl silanes, offer enhanced reactivity and modified regioselectivity due to substrate and catalyst dependent electronic control. For example, a bulky Ti complex affords the linear product with dimethylphenylvinylsilane, while Ta hydroaminoalkylation catalysts offer mixtures of regioisomers with vinylsilane substrates. , …”
supporting
confidence: 82%
“…In the formation of intermediate D two diastereomers can result ( D and D′ ), with the trans-orientation of the metallacyclic intermediates giving the major diastereomer . This is consistent with computational investigations of early transition-metal-catalyzed hydroaminoalkylation , which propose that polarized, activated alkenes, such as vinyl silanes, offer enhanced reactivity and modified regioselectivity due to substrate and catalyst dependent electronic control. For example, a bulky Ti complex affords the linear product with dimethylphenylvinylsilane, while Ta hydroaminoalkylation catalysts offer mixtures of regioisomers with vinylsilane substrates. , …”
supporting
confidence: 82%
“…For intermediate J , both cis and trans isomers could form. Previous computational studies on early transition metal catalyzed HAA suggest that alkene insertion is under electronic control and depends on the polarization of the double bond of the alkene and the identity of the metal center in the transition state [16, 23] . This work shows that steric parameters also play a role with this zirconium catalyst.…”
Section: Resultsmentioning
confidence: 55%
“…Previous computational studies on early transition metal catalyzed HAA suggestt hat alkene insertion is under electronic control and depends on the polarization of the double bond of the alkene and the identityo ft he metal centeri nt he transition state. [16,23] This work shows that steric parameters also play ar ole with this zirconium catalyst. Literature reports on tantalum [24] and titanium [13] HAA with vinylsilane show the formation of mixture of regioisomers or exclusive formation of the linear product, respectively.T od ate, steric effectsd ominate over electronic parameters in zirconium catalyzed reactivity.…”
Section: Entrymentioning
confidence: 74%
“…Substrate electronic properties have a notable effect on reaction productivity, in which electron rich, pi‐donating substituents typically result in higher reaction conversions. This is proposed to be due to the increased amine nucleophilicity resulting in improved coordination to promote associative protonolysis of Ta−C bonds in the turnover limiting step of the catalytic cycle ( vide infra , Figure ) …”
Section: Resultsmentioning
confidence: 99%
“…The alkene insertion is a key step in defining the regiochemistry and stereochemistry of the final product. Recent computational chemistry investigations of the mechanism of hydroaminoalkylation showed that regioselectivity is affected by electronic effects consistent with the build‐up of partial positive charge on the more substituted carbon during the alkene insertion step …”
Section: Resultsmentioning
confidence: 99%